Psychological violence against women in the Andean regional narrative - Rodríguez-Berrocal, Pío (2022)
The purpose is to show the humorous and sexist elements, as forms of psychological violence against women, in the literary discourse of the book Taita Serapio (2004). In the stories, the humor with which the stories are seasoned and machismo stand out as powerful ways to attack the psychological integrity of women. The male character embodied in Taita Serapio, a sarcastic and perverted individual, sees in each woman an instrument of sexual satisfaction and mockery. In essence, Taita Serapio is characterized as a character with certain sexual deviations reaching a vague exhibitionism. In this work, literary criticism and analysis are applied to show how Zuzunaga constructs humor, hand in hand with machismo, from the grotesque or inconsequential in the circumstances and in the controversies of the protagonists. Fundamentally, the study is oriented through the theory of psychoanalytic literary criticism, as well as anthropological theory, to analyze the topics raised.